Correlation between BMI and ADLs with Mental Emotional Disorder among Elderly - Nabilah Qonitah; Muhammad Atoillah Isfandiari (Universitas Airlangga, 2015)
Increased life expectancy causes an increase in the number of elderly people. In the aging process, various things occur that cause various bodily functions to decline which can cause various health problems and are risk factors for mental-emotional disorders. This study was conducted to determine the relationship between Body Mass Index (BMI), physical independence, and the characteristics of the elderly with emotional mental disorders in the elderly in the Jombang Elder Social Care Unit in Kediri. This type of research is an analytic study using a cross-sectional study design. Interviews were conducted with 47 people using simple random sampling. The dependent variable in this study is mental-emotional disorders. The independent variables are characteristics, BMI, and physical independence. Data analysis was performed with Chi-square and Pearson correlation. The prevalence of mental-emotional disorders found in this study was 23.4%. Respondents who did not have physical independence were 4.3%. Respondents who have an abnormal body mass index are 26.2%. The results showed that physical independence had a significant relationship with mental-emotional disorders (p = 0.008). The conclusion from this study is that the elderly have the risk of suffering from emotional mental disorders. Physical independence is associated with mental-emotional disorders in the elderly, so there needs to be more attention especially from the psychological side of the elderly who do not have physical independence.